Microplastics presence in cultured and wild-caught cuttlefish, Sepia officinalis. (November 2020) - Oliveira, Ana R.; Sardinha-Silva, Andreia; Andrews, Paul L.R.; Green, Dannielle; Cooke, Gavan M.; Hall, Sarah; Blackburn, Kirsty; Sykes, António V.
Abstract: Amongst cephalopods microplastics have been reported only in jumbo squid gut. We investigated microplastics in the digestive system of wild cuttlefish ( Sepia officinalis ) as they are predators and prey and compared the stomach, caecum/intestine and digestive gland (DG) of wild and cultured animals, exposed to seawater from a comparable source. Fibers were the most common type (≈90% of total count) but were ≈2× higher in relation to body weight in wild vs. cultured animals. Fibers were transported to the DG where the count was ≈2× higher /g in wild (median 1.85 fibers/g) vs. cultured. In wild-caught animals the DG was the predominant location but in cultured animals the fibers were more evenly distributed in the digestive tract. The potential impact of microplastics on health of cuttlefish is discussed. Cuttlefish represent a previously unrecognized source of microplastic trophic transfer to fish and finding fibers in cultured animals has implications for aquaculture. Highlights: Microplastics were found in the digestive tract/digestive gland of wild and cultured cuttlefish. Fibers were the predominant type (~90% total count) in both wild and cultured cuttlefish. Plastic fragments, beads and microfilm pieces were also found in animals from both sources. The fiber count/g digestive gland of wild-caught animals was twice that of the cultured animals. The potential implications for cuttlefish health, trophic transfer and aquaculture are reviewed.